Dual Ice Crystal Imager (D-ICI): images of snow particles, Kiruna, 2014 - Dual Ice Crystal Imager (D-ICI): images of snow particles from Kiruna on 2014-10-19 with size, area, and fall speed measurements - Kuhn, Thomas (Luleå University of Technology, 2019)
Accurate predictions of snowfall require good knowledge of the microphysical properties of the snow ice crystals and particles. Shape is an important parameter as it influences strongly the scattering properties of the ice particles, and thus their response to remote sensing techniques such as radar measurements.
The fall speed of ice particles is another important parameter for both numerical forecast models as well as representation of ice clouds and snow in climate models, as it is responsible for the rate of removal of ice from these models.

A new ground-based in-situ instrument, the Dual Ice Crystal Imager (D-ICI), has been developed to determine snow ice crystal properties and fall speed simultaneously. The instrument takes two high-resolution pictures of the same falling ice particle from two different viewing directions.
Both cameras use a microscope-like set-up resulting in an image pixel resolution of approximately 4μm/pixel. One viewing direction is horizontal and is used to determine fall speed by means of a double exposure. For this purpose, two bright flashes of a light-emitting diode behind the camera illuminate the falling ice particle and create this double exposure and the vertical displacement of the particle provides its fall speed. The other viewing direction is close to vertical and is used to provide size and shape information from single-exposure images.
This viewing geometry is chosen instead of a horizontal one because shape and size of ice particles as viewed in the vertical direction are more relevant than these properties viewed horizontally as the vertical fall speed is more strongly influenced by the vertically viewed properties.
In addition, a comparison with remote sensing instruments that mostly have a vertical or close to vertical viewing geometry is favoured when the particle properties are measured in the same direction.

The instrument has been tested in Kiruna, northern Sweden (67.8N, 20.4E). First measurements from 2014-10-19 are presented with images and determined snow ice crystal properties.

The dataset is the basis of Kuhn, T. and Vázquez-Martín, S.: Microphysical properties and fall speed measurements of snow ice crystals using the Dual Ice Crystal Imager (D-ICI), Atmos. Meas. Tech., 13, 1273–1285, https://doi.org/10.5194/amt-13-1273-2020, 2020.

The data consist of images of individual snow crystals or snowflakes taken by the two cameras of D-ICI. Images from the top-view camera are in the folder named "20141018_180609_top" and the side-view images in the folder "20141018_180728_side". The folder of top-view images contains a subfolder called "detected" that contains results from image processing to detect particles and determine their edge, size (maximum dimension), and cross-sectional area (area inside boundary). These results consist of images where the background (first image in folder "20141018_180609_top") is removed (in folder "bck_removed"), black-and-white images where black marks detected snow particles (in folder "bw"), images representing the used Sobel gradient matrix (in folder "bw", file name contains "gm"), particle cut-out images (in folder "particles"), particle cut-out images with the particle edge visualized (in folder "borders"). In addition, the file "particles_output.txt" lists Particle name (image name including a running number starting at 1 for all particles found on the same image), area (in number of pixels), size (maximum dimension in number of pixels), and area ratio. The file "particles.log" is a log file from image processing containing information (described in the header), for example the maximum gradient of the Sobel gradient matrix.
The side-view images in the folder "20141018_180728_side" show double exposures of the snow particle, from which the fall speed is determined. Apart from very few exceptions where one of the cameras missed to take an image, each side-view image has a corresponding top-view image taken at the same time. However, the timestamps are not identical (but usually within one second) as the two computers saving the data were not exactly synchronized.

Four text files contain size, area and fall speed data derived from images and used for Area versus Maximum dimension and Fall speed versus Maximum dimension figures:

Size and area data:
20141018_all_particles.txt
Columns contain:
1: imagename
2: particlename
3: dmax/um (micrometre)
4: area/m2
5: Ar (area ratio)
6: m09/kg (particle mass determined from Schmitt and Heymsfield (2009), Eq.2.
7: date_time

Size and fall speed data:
20141018_fallspeed.txt
Columns contain:
1: speed_y/(m/s)
2: folder
3: particle_name
4: max_dimx (maximum width in x direction in pixels)
5: max_dimy (maximum width in y direction in pixels)
6: area(px)
7: area/m2
8: Dmax(px)
9: Dmax/um (micrometre)
10: area_ratio

Same data but only for particles of certain shapes is contained in:
droplets_20141018.txt: droplets
needles.txt: needles and agglomerates of needles
rimed.txt: rimed particles

References:
Schmitt and Heymsfield (2009), J. Atmos. Sci., 66 (7), pp2013-2028.

Ett nytt instrument, kallad Dual Ice Crystal Imager (D-ICI), har utvecklats för att mäta samtidigt mikrofysikaliska egenskaper och fallhastighet av snöpartiklar. Instrumentet tar bilder av partiklar från två olika riktningar med en upplösning av 4μm/pixel. Första mätningar med D-ICI i Kiruna, norra Sverige (67.8N, 20.4E), den 2014-10-19 presenteras. Både bilder och egenskaper framtagna av dessa ingår i datasetet.

Datasetet ligger till grund för artikeln Kuhn, T. and Vázquez-Martín, S.: Microphysical properties and fall speed measurements of snow ice crystals using the Dual Ice Crystal Imager (D-ICI), Atmos. Meas. Tech., 13, 1273–1285, https://doi.org/10.5194/amt-13-1273-2020, 2020.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1129

Data består av bilder från två kameror, top view och side view. Bilderna finns i mappar "20141018_180609_top" (top view) och "20141018_180728_side" (side view). Mappen av top-view bilder innehåller också resultat från bildanalys för att hitta snöpartiklar samt deras kant, storlek och yta.
Fyra textfiler innehåller storlek, yta och fallhastighet av snöpartiklarna.

För mer information se den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1129
Dual Ice Crystal Imager (D-ICI): bilder av snöpartiklar från Kiruna, 2014 - Dual Ice Crystal Imager (D-ICI): bilder av snöpartiklar från Kiruna den 2014-10-19 med storlek, yta, och fallhastighetsmätningar
Keywords: snow; snö; Atmospheric conditions; Atmosfäriska förhållanden; snow crystals; snökristaller; snow fall; snöfall; snow fall speed; snöfallshastighet; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi